Effectiveness of fourth-line dual immunotherapy in hepatocellular carcinoma with simultaneous steroid administration for immune-related hepatitis. (February 2022) - Lowes, Kristina; Reinecke, Johanna; Brunner, Marius; Scholz, Matthias; Kitz, Julia; Michels, Beate; Mekolli, Ardian; Gaedcke, Jochen; Seif Amir Hosseini, Ali; Ströbel, Philipp; Ghadimi, Michael; Ellenrieder, Volker; et al.
Medical therapy of advanced hepatocellular carcinoma (HCC) remains an emerging subject, but therapeutic sequences together with toxicity management are rarely described. Herein, we report the case of a therapeutic sequence and toxicity management in a 72-year old White male with advanced non-cirrhotic HCC. The HCC of this patient was refractory against treatment with several tyrosine kinase inhibitors, including lenvatinib and cabozantinib or immune combination of pembrolizumab and lenvatinib. Double immune combination of nivolumab and ipilimumab was effective in fourth-line treatment but resulted in immunotherapy-related grade 4 hepatitis. This toxicity responded well to high doses of corticosteroids, and reinduction of dual immune combination remained effective despite continuation of high-dose corticosteroids in a non-cirrhotic HCC. This case demonstrated the efficacy of double immune therapy in higher treatment lines in advanced non-cirrhotic HCC even if the patient was treated with other immune modulatory therapies earlier. Moreover, it can remain effective under concomitant administration of high-dose corticosteroids.